Evaluasi Penggunaan Obat Glimepirid Pada Pasen Diabetes Melitus Tipe 2 Di RS Tamar Medical Centre Pariaman - Humaira, Vilma; Gusnelti, Yesi; Abeiasa, M. Saka; Fadya Syafitri, Aqilla (Universitas Sumatera Barat, 2024)
Evaluation of the use of diabetes mellitus type 2 drugs at Tamar Medical Center Pariaman Hospital aims to determine usage patterns and evaluate the rationality (appropriateness) of using antidiabetic drugs. The research method used is descriptive with direct data sampling. A total of 30 samples were evaluated, the conclusion of this research is that from the first ten points regarding the correct dose, from 30 respondents, 80.64% (25 people) had used the correct dose of medication and 19.36% (5 people) had not used the correct dose at Tamar Hospital. medical pariaman and from the second ten points about the right way to use it, from 30 respondents 59.31% (18 people) had the right way to use the drug glimepiride, 40.69% (12 people) did not use the medicine correctly and from the third ten points about the right time 85.62% (27 people) were on time when using glimepirid, 14.38% (3 people) were not using glimepiride on time)